The soil microbiomes of forest ecosystems in Kenya: their diversity and environmental drivers - Onyango, L.A.; Ngonga, F.A.; Karanja, E.N.; Kuja, J.O.; Boga, H.I.; Cowan, D.A.; Mwangi, Kennedy Wanjau; Maghenda, M.W.; Lebre, P.B.N.M.; Kambura, A.K. (Springer, 2023)
Soil microbiomes in forest ecosystems act as both nutrient sources and sinks through a range of processes including organic matter decomposition, nutrient cycling, and humic compound incorporation into the soil. Most forest soil microbial diversity studies have been performed in the northern hemisphere, and very little has been done in forests within African continent. This study examined the composition, diversity and distribution of prokaryotes in Kenyan forests top soils using amplicon sequencing of V4-V5 hypervariable region of the 16S rRNA gene. Additionally, soil physicochemical characteristics were measured to identify abiotic drivers of prokaryotic distribution. Different forest soils were found to have statistically distinct microbiome compositions, with Proteobacteria and Crenarchaeota taxa being the most differentially abundant across regions within bacterial and archaeal phyla, respectively. Key bacterial community drivers included pH, Ca, K, Fe, and total N while archaeal diversity was shaped by Na, pH, Ca, total P and total N. To contextualize the prokaryote diversity of Kenyan forest soils on a global scale, the sample set was compared to amplicon data obtained from forest biomes across the globe; displaying them to harbor distinct microbiomes with an over-representation of uncultured taxa such as TK-10 and Ellin6067 genera.